Preparation, characterization and thermal reliability of form-stable Myristic acid/Polypyrrole composites as phase change materials for thermal energy storage - Silakhori M.; McTselaar H.S.C.; Mahlia T.M.I.; Fauzi H. (Association for Iron and Steel Technology, AISTECH, 2023)
A novel form-stable Myristic acid (MA)/Polypyrrole (PPy) phase change materials (PCMs) were readily synthesized by in-situ polymerization method. MA and PPy were used as thermal energy storage material and supporting material, respectively. SEM (Scanning electron microscopy) and FTIR (Fourier transform infrared spectrometer) were illustrated MA Particles were wrapped by PPy particles. Differential scanning calorimetry(DSC) were used for investigating thermal energy storage properties of prepared form-stable PCMs. The form-stable PCMs were considered as the highest loading PCM with desirable latent heat storage and good thermal stability. Thermal cycling tests were done up to 2500 cycles which showed form-stable PCMs had a favorable thermal reliability. Thanks to favorable thermal properties, thermal stability and chemical stability, the new type of form stable PCMs can be considered for low temperature thermal energy storage applications. Copyright © 2014 MS&T14®.